Crystallization behaviour of neodymium doped yttrium silicate nanophosphors - TAV, CUMALİ; ERDEM, MURAT (ELSEVIER SCI LTD, 2011)
Sol-gel technique was used to prepare yttrium silicate powders doped with 0.01Nd(3+). The crystallite sizes were determined to be 23 +/- 0.5 nm from the XRD patterns of the powders annealed at 960 degrees C. The Y(4.67)(SiO(4))(3)O, Y(2)Si(2)O(7) and Y(2)SiO(5) crystalline phases were observed upon heat treatment at 960 degrees C which is much lower than 1500-1650 degrees C are reported before. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Yttrium silicate; Nanophosphors; Sol-gel processes; Y2SIO5